An Assessment of the Investment Climate of the Russian economy ("Journal "U". Economy. Management. Finance.", 2021)
The problem of insufficient investment in the Russian economy is quite acute, so the article presents an assessment of the investment activity of both domestic and foreign investors in enterprises of the Russian economy. The dynamics of the index of physical volume of investments in fixed assets is considered, and conclusions are drawn about the investment climate in the Russian Federation.
Keywords: investment; investment climate; business; industry